PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP RETENSI KARYAWAN DI PT LIQUID KENCANA ABADI KOTA GUNUNGSITOLI - Waruwu, Jesslyn Felicia; Telaumbanua, Eliagus; Waruwu, Meiman Hidayat; Duha, Tiarni (Jurnal Suluh Pendidikan, 2025)
Employee retention is a technique used by a company or organization to retain employees for a longer period. Employee retention is very important for companies because losing experienced and quality employees can negatively impact the organization and significantly affect its performance and productivity. This is also true for PT Liquid Kencana Abadi located at Jalan Diponegoro 346, Ilir, Kec. Gunungsitoli, Gunungsitoli City, North Sumatra. This study aims to determine the effect of compensation on employee retention at PT Liquid Kencana Abadi in Gunungsitoli City. This research employs a quantitative method, with respondents consisting of 35 employees from PT Liquid Kencana Abadi in Gunungsitoli City. The researcher collected data using a questionnaire and then conducted validity and reliability tests, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test), simple linear regression,coefficient of determination, t-test, and f-test. The results indicate that the influence of compensation and job satisfaction on employee retention at PT Liquid Kencana Abadi in Gunungsitoli City is 79.6%, while 20.4% is influenced by other factors not addressed in this study.